واقع لحم الفرّوج المسوّق بين الجانب التكنولوجي وآلية التسعير - موسى, أمين (Latakia University Journal -Biological Sciences Series, 2018)
أُنجزت هذه الدراسة المساهمة لتسليط الضوء على واقع تسويق لحم الفروج من منافذ البيع التابعة للمؤسسة العامة للدواجن إضافة للمحلات الخاصة. وقد هدفت الدراسة توضيح نقطتين هامّتين. الأولى وهي الطريقة المختارة من قبل المؤسسة وغيرها لتقطيع وبيع ذبائح الفروج ولحمه. والثانية تتضمّن العملية المُنجزة لطرق ذبح الفروج وتصنيع الذبيحة ونقلها. ودليلاً على جودة العملية التكنولوجية اُختير المؤشرٍ الميكروبيولوجي وجرى اختباره. لقد أوضحت عملية تقطيع الذبائح التي اختيرت وسمّت القطع "فخذ الفروج وصدر الفروج" أنَّها تضمنت تضليلاً. جرى تقطيع العينات ووزن القطع الناتجة، ثم فُصل اللحم عن العظم (تشفية اللحم) وتمَّ وزنهما أيضاً. أمّا الاختبار المكروبيولوجي فقد نُفذ شهرياً. وقد بينت نتائج هذا الاختبار أنَّ عملية تقطيع وتسويق ذبائح الفروج قد جرت تحت ظرفٍ من الإهمال الواضح للأمور الصحية. أُجري تقويم إحصائي ورياضي للعلاقة بين كلِّ قطع الذبيحة (فخذ، صدر، رقبة، مُقدم القطعة الظهرية، مؤخر القطعة الظهرية، الأجنحة) و الوزن الكلّي للذبيحة، فأظهر أنَّ العلاقة بينها يُمكن أن يُعـبّر عنها بأنموذج رياضي (موديل رياضي). المعادلة الرياضية التي تصف العلاقة هي من الشكل: Y= b1 X + b2 X2 + b3 X3. معامل الارتباط لجميع المعادلات الرياضية كان مرتـفعاً (بين 0.988 - 1.000)، ممّا يعكس جودةً في التعبير عن العلاقة القائمة. وقد عُولجت عملية تسعير الذبائح وقطعها، ووجد أنَّ التسعير المُعطى للقطع لم يكن عادلاً. من خلال هذا العمل جرى توضيح واقتراح طريقة تقطيع جديدة وكذلك طريقة تسعير صحيحة وعادلة. This study was carried out in order to cast light on the status of one the government establishments, marketing chicken carcasses as well as on that of private shops. The study amid to highlight two points. The first one is the carcasses cutting method, which was selected for selling chicken-meat products. The second is the conducted process of chicken slaughtering and carcasses processing. For good conducted process, a microbiological index was selected and inspected. Carcass cutting process indicates that the parts named "chicken leg" or "chicken breast" were deceptively named. Samples of chicken carcasses were weighed and cut. In each part, meat was separated from bones, and both were weighed. A microbial test was monthly implemented. Data of microbial test data show that the processed and marketed chicken carcasses and chicken parts were processed under very hygienically poor conditions. Statically and mathematically estimated correlation between the total weight of the carcass and the weight of carcass parts shows that this relationship can be expressed in a mathematical model. The mathematical equation which describes the relationship has the form: Y= b1 X + b2 X2 + b3 X3. Correlation coefficient in all suggested equations was very high (between 0.988 - 1.000). The correlation well reflects the existing relationship. These equations can be used for finding each carcass part weight from carcass total weight and visa versa. The process, which prices chicken carcass parts, was treated. An unfair price was given for these parts. This research suggests a new cutting method as well as a just and correct pricing method.